Japanische Regionalzentren im Prozess der Binnenwanderung - Schöller, Peter (ERDKUNDE, 1970)
This study, a continuation of Internal Migration and Urban Growth in Japan (Erdkunde Bd. 22, 1968, p. 13-29) inquires after the role of the regional, non-metropolitan centers in the process of industrialization, urban growth and migration. An analysis of the pattern of migration in Hokkaido and the Western Inland Sea reveals that there is a hierarchic structure of the country - town/ city and town/ city - city migration. It is not the monofunctional industrial cities, but the multifunctional central cities, which are the chief forces of development. The Tokyo type of internal migration is indeed repeated on a lower level. Immigration from other cities as compared with rural areas is the more prevailing, the more functions the center of immigration possesses. Immigration from distant rural districts is often only a temporary phenomenon. Apart from the expectation of an economic and social upgrading immigration into the regional centers seems to be chiefly motivated by better educational conditions; urban off-time entertainment and the general modernity of life. Housing conditions, extra-urban entertainment and the surrounding landscape of the chosen place are apparently only of minor importance.